Prosthetic hysteria staging the cold war in Filipino/American docudrama - Capino, Jose B. (2004)
This paper explicates docudrama about the Cold War in the Philippines produced during the 1950s. The films, a documentary and a feature film, both funded and scripted by Washington but staged by leading Filipino filmmakers and actors, fabricated Cold War panic by hybridizing the transnational codes of melodrama with the discursive truth claim (i.e. evidentiary force) of documentary cinema. The resulting syncretic cinematic practice, to which the contemporary term docudrama may be productively applied, is in many registers both doubled (e.g., double-voiced) and split (e.g., stylistically bifurcated), and thus riddled with both ideological and formal issues.
Includes bibliographical references (pages 14).
Keywords: Capino,Jose B; Cold war in motion pictures